2005
DOI: 10.1016/j.febslet.2005.03.092
|View full text |Cite
|
Sign up to set email alerts
|

A novel neurotrophic role of secretory phospholipases A2 for cerebellar granule neurons

Abstract: Cultured cerebellar granule neurons (CGNs) require membrane depolarization or neurotrophic factors for their survival in vitro and undergo apoptosis when deprived of these survival-promoting stimuli. Here, we show that secretory phospholipases A 2 s (sPLA 2 s) rescue CGNs from apoptosis after potassium deprivation. The neurotrophic effect required the enzymatic activity of sPLA 2 s, since catalytically inactive mutants of sPLA 2 s failed to protect CGNs from apoptosis. Consistently, the ability of sPLA 2 s to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 53 publications
1
15
0
1
Order By: Relevance
“…It was evident that the action of PLA 2 and BPB-PLA 2 is mediated by ROS generated from NADPH oxidase. channel Yagami et al, 2003a,b;Arioka et al, 2005]. As illustrated in Figure 7A,B, it showed that [Ca 2þ ]i was notably increased after treatment with PLA 2 and BPB-PLA 2 for 30 min and then declined to the level indistinguishable from that of untreated control cells.…”
Section: P38 Mapk Activation and Upregulation Of Fas And Fasl Are Evomentioning
confidence: 78%
“…It was evident that the action of PLA 2 and BPB-PLA 2 is mediated by ROS generated from NADPH oxidase. channel Yagami et al, 2003a,b;Arioka et al, 2005]. As illustrated in Figure 7A,B, it showed that [Ca 2þ ]i was notably increased after treatment with PLA 2 and BPB-PLA 2 for 30 min and then declined to the level indistinguishable from that of untreated control cells.…”
Section: P38 Mapk Activation and Upregulation Of Fas And Fasl Are Evomentioning
confidence: 78%
“…This, postulated role of sPLA 2 -IIA as a secreted neuromodulator during synaptic transmission seems consistent with previous findings that sPLA 2 plays role in membrane depolarization and Ca 2+ entry, necessary for maintenance of healthy neurons: cerebellar granule neurons require membrane depolarization and neurotrophic factors to survive in vitro, and sPLA 2 was shown to protect these neurons from apoptosis caused by K + deprivation. Moreover, the ability of sPLA 2 to promote neuronal survival is inhibited when extracellular Ca 2+ is depleted or when Ltype Ca 2+ channel is blocked by nicardipine (Arioka et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Several mammalian sPLA 2 s have been shown to stimulate cell proliferation in cancer cells [18,19,22,25]. An anti-apoptotic role in growth factor-deprived cells has been shown for the group IIA in kidney fibroblasts [65], and for the group III and X sPLA 2 s in neuronal cultures [66,67]. The enzymatic activity-dependent mechanisms reported [18,22,65] have usually been associated with the pleiotropic actions of AA-derived eicosanoids [25] and rarely with lysophospholipids [26,66].…”
Section: Discussionmentioning
confidence: 99%